2014
DOI: 10.1007/s00590-014-1507-z
|View full text |Cite
|
Sign up to set email alerts
|

Is acetabular osteoplasty always required in mixed impingement?

Abstract: Satisfactory clinical outcomes were seen in hips with mixed impingement, regardless of whether RT was performed, provided impingement-free functional motion was attained and no severe cartilage damage was seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Whereas two studies demonstrated superior alpha angle correction in surgical hip dislocation 27,32 , another study found arthroscopy produced superior correction 20 , with the remaining two studies showing no significant between group differences 17,28 . Four studies comparing different arthroscopic techniques 23,24,30,33 and one study comparing different open surgeries 26 showed significantly decreased alpha angle in both groups without significant betweengroup differences. The alpha angle was corrected to below 50 in seven studies 17,20,26e28,32,33 , while in three studies post-operative alpha angle remained at levels diagnostic of FAI (i.e., >50 ) in all or a significant number of participants 27,28,30 .…”
Section: Symptom Outcomes After Different Open Surgical Techniquesmentioning
confidence: 98%
See 2 more Smart Citations
“…Whereas two studies demonstrated superior alpha angle correction in surgical hip dislocation 27,32 , another study found arthroscopy produced superior correction 20 , with the remaining two studies showing no significant between group differences 17,28 . Four studies comparing different arthroscopic techniques 23,24,30,33 and one study comparing different open surgeries 26 showed significantly decreased alpha angle in both groups without significant betweengroup differences. The alpha angle was corrected to below 50 in seven studies 17,20,26e28,32,33 , while in three studies post-operative alpha angle remained at levels diagnostic of FAI (i.e., >50 ) in all or a significant number of participants 27,28,30 .…”
Section: Symptom Outcomes After Different Open Surgical Techniquesmentioning
confidence: 98%
“…Change in symptoms in young patients (mean age 24e30 years) following surgical hip dislocation was compared in two retrospective cohort studies 26,29 . One study comparing open surgical labral resection and labral refixation found that both groups improved significantly from baseline to 24 months with the refixation group showing greater improvements, and that participants undergoing surgical hip dislocation had better outcomes if the acetabular labrum was reattached rather than resected 29 . The other study compared outcomes in patients with pure cam deformity where only a femoral osteochondroplasty was performed, and those with comorbid pincer impingement where acetabular rim trimming, labral takedown and labral refixation was also performed 26 . Both groups experienced significant improvement in pain scores, while only the osteochondroplasty alone group had significant improvement in function 26 .…”
Section: Symptom Outcomes After Different Open Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the femoral torsion and the real acetabular version, computed tomography was performed. 24,25 The acetabular version was found to be of 11° at the proximal acetabulum,…”
Section: Case Reportmentioning
confidence: 97%
“…No intra-or extra-articular impingement was found by testing the hip intraoperatively (flexion-extension: 100°/0°/5°; internal-external rotation: 35°/0°/50°), and this was attributed to the excessive femoral antetorsion that slightly compensated the low proximal acetabular version. Thus, we decided only to trim the Figure 3 CT-scan with measurement of the acetabular version angle from proximal to center of the head according to Hingsammer et al 24 acetabular rim minimally and perform an acetabular labral repair by means of five bioabsorbable anchors followed by a correction and smoothing of the head-neck offset indentation.…”
Section: B a B Amentioning
confidence: 99%